Membuka Kunci Keberhasilan Akuisisi Bakat: Analisis Jalur Variabel Rekrutmen dan Seleksi yang Berdampak pada Kinerja Karyawan dan Hasil Organisasi - I.G.A. Aju Nitya Dharmani (AKUNTANSI 45, 2026)
This study aims to partially or simultaneously examine the factors that affect the performance of teachers and employees at SMA Negeri 2 Mojokerto City. The research method uses a quantitative approach with a population of 73 people, consisting of teachers and employees, which is determined through total sampling techniques. Data was collected through surveys using questionnaire instruments and analyzed with SmartPLS software to identify the influence of the variables studied. The results of the study show that certain factors, especially selection criteria and recruitment experience, have a significant influence on the performance of teachers and employees. Simultaneous analysis also showed the collective contribution of these variables to performance improvement. However, this study has limitations in the relatively small sample scope and analysis methods used, so the results cannot be generalized widely. Therefore, follow-up research is recommended to expand the scope of the sample by involving more schools and using more comprehensive analysis methods to gain a deeper understanding of the factors that affect the performance of educators and education staff. These findings are expected to be the basis for the development of recruitment policies and human resource management in schools.